Burden among Caregiver of End Stage Renal Disease Patient Undergoing Hemodialysis at Tertiary Care Hospital of Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: With a huge number of people being care dependent with most of the caregivers being informal and primarily female, the emotional, physical, social, and financial burden increases for the caregivers. End-stage renal disease (ESRD) is a major cause of elderly patients admitted to hospitals, mostly relying on hemodialysis. Their caregivers are at high risk of having moderate to severe burdens. Zarit’s burden scale is a verified 22-item Linkert scale questionnaire that is reliable to measure burden in people who have been caretakers for over a year, have some financial burden, and are a family member. Materials and Methods: Caretakers of hemodialysis patients (55 in number) were included in the survey at the Nephrology unit of Nobel Medical College and Teaching Hospital. Zarit’s Burden scale was weighted against age, sex, religion, education, occupation, family type, marital status, and relationship with the patient, and the severity of the burden was estimated.Results: 69.1% of the caretakers had moderate to severe burden with more than half (65.5%) of caretakers over 40 years of age. 60% of the caretakers were female. More than 2/3rd (70.9%) of caretakers were the significant other of the patient. A significant relation between age, occupation, and relationship with the patient was found with the level of burden present.Conclusions: The study reveals the status of caretakers of hemodialysis patients in eastern Nepal. The study reveals differences in caretaker demographics and level of burden being largely affected by age, occupation, and relationship.